PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN KSP WISUDA GUNA RAHARJA - R. Made Ratmara; A.A. Ketut Sri Asih; Ni Nyoman Ayu Suriyani (Universitas Triatma Mulya, 2022)
Every organization has human resources which are the most important assets for the company, where these resources have the ability to develop in determining the company's success for the long term. Human resources are a central factor in an organization. Whatever the form and purpose, the organization is founded on a vision for the common good, and in carrying out its mission is managed by humans. Manpower or employees are the most valuable resources in the organization, without qualified employees, the goals of the organization will not be achieved properly. This study aims to: 1) determine the effect of leadership style on employee performance, 2) determine the effect of work motivation on employee performance, 3) the magnitude of the influence of leadership style and work motivation on employee performance, and 4) independent variables that have a dominant influence on employee performance at ksp graduation guna raharja denpasar. The population of this study were all employees at ksp graduation guna raharja denpasar, amounting to 59 people. The sample taken is all members of the population so that it is a census study. The analytical tool used is multiple linear regression analysis. The hypothesis test used is t-test to test the partial effect of leadership style and work motivation on performance, as well as determination analysis to analyze the magnitude of the influence of the independent variable on the dependent variable. The regression equation obtained is: y= 17.939 + 0.316 x1 + 0.762 x2. This model shows that: 1) there is a positive and significant influence of leadership style on employee performance, 2) there is a positive and significant influence of work motivation on employee performance, 3) the magnitude of the influence contributed by leadership style and work motivation on employee performance is 23.2 %, and 4) work motivation is a variable that has a dominant influence on employee performance at ksp graduation guna raharja denpasar.